Case of successful treatment of bilateral acanthamoeba keratitis (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Acanthamoeba keratitis is related to a severe pathology of the eye that results from infection of the human body by free-living amoeba in soil. This disease is characterized by loss of the corneal epithelium, stromal thinning, and development of radial keratoneuritis, appearance of the annular infiltration and formation of a central or paracentral corneal abscess.Purpose. To describe a case of successful treatment of bilateral acanthamoeba keratitis where standard therapy was first supplemented with photodynamic therapy (PDT) using methylene blue and dimexid.Material and Methods. There were used test of visual acuity, ophthalmoscopy, microbiological analysis.»Results. Complex treatment of bilateral acanthamoeba keratitis, which includes different antiseptics, antifungal, amebicidal drugs, the use of pathogenetic and symptomatic therapy, and the use of PDT with methylene blue and dimexid allowed to stop inflammation and restore vision.Conclusions. In the diagnosis of acanthamoeba keratitis the important role belongs to the anamnesis, biomicroscopy of the cornea with the identification of pseudodendritical figures or recurrent epithelial damage, which are the earliest clinical signs of the disease.Combined treatment of this disease in combination with PDT first used in the ophthalmic practice showed significant therapeutic effect.
Keywords: akanamebny keratitis; photodynamic therapy; methylene blue; dimeksid